BEBERAPA JENIS PALEM YANG BERPOTENSI SEBAGAI TANAMAN PENGISI RUANG TERBUKA HIJAU - L. Pangemanan L. Pangemanan,dkk (EKOTON, 2013)
Palm as a group of plants, very interesting. Interesting, not in terms of botany, but also in terms of beauty of form, diversity of species and its use. This is possible because the groups are large amounts of palm. It is estimated that, in this world is growing at about 2800 species of palm that belong to 215 genera. Of these, Indonesia has approximately 460 species of about 35 genera (Setijati Sastrapradja, 1980). Of course not all known palm grows in Indonesia, known to his name. Thus, there is still a chance to discover a new species from the forests of Sumatra, Sulawesi, Kalimantan, Irian Jaya or the small islands that munkgin still has areas of natural woodland. The types of benefits are not yet known, nor the less obvious forms of her body, could have escaped.